Design and Development of a Distance and Heart Rate Monitoring System for a Dynamic Bicycle - Anggara Trisna Nugraha; Muhammad Jafar Shiddiq (Journal of Marine Electrical and Electronic Technology, 2024)
Air is a vital resource for human life and the ecosystem, playing a crucial role in sustaining living beings. Its quality directly impacts health and well-being, making it essential to preserve and monitor air for safe usage. Air pollution, which results from the degradation of air quality, poses significant health risks, prompting individuals to engage in physical activities such as jogging, marathons, futsal, and cycling. Among these, cycling is favored not only as a recreational activity but also as a sustainable mode of short-distance transportation, offering both physical health benefits and environmental advantages. In this study, we present the design and development of a dynamic bicycle system equipped with a distance and heart rate monitoring mechanism. The proposed system integrates cutting-edge sensor technology, including the MAX30102 optical heart rate sensor and the M8N GPS module, to provide real-time data on cyclist performance. This research aims to contribute to both engineering and health domains by addressing the dual objectives of enhancing physical fitness and supporting eco-friendly transportation. During the testing phase, the system demonstrated challenges in sensor noise and data accuracy. For instance, the MAX30102 sensor exhibited rapid fluctuations due to program-related noise and environmental factors, necessitating the implementation of advanced filtering techniques such as the Kalman filter to stabilize readings. Similarly, the M8N GPS sensor showed a 2-meter deviation in distance measurements, which, although acceptable for odometer functionality, requires optimization to improve precision during signal loss scenarios.